What Drives Private Savings in Malaysia? - Tang, Chor Foon; Tan, Eu Chye; Chua, Soo Y. (Taylor & Francis, 2020)
This research attempts to reassess the long-run determinants of private savings in Malaysia using the cointegration and variance decomposition methods. This study covers annual data from 1980 to 2016. We find that private savings would increase together with the private disposable income, modified dependency ratio, and financial sector development. Results also reveal that the female–male sex ratio and macroeconomic uncertainty have a negative impact on private savings in Malaysia. Besides, the results show that disposable income, the sex ratio, financial sector development, and macroeconomic uncertainty are relatively more important than the other variables in determining Malaysia’s private savings. ©, Copyright © Taylor & Francis Group, LLC.